Towards the privatization of global forest governance?. (1st September 2008) - Guneau, S; Tozzi, P
Faced with the fragmentation and the weakness of international forest regimes, new forms of global governance have emerged over the last 15 years through the creation of private transnational certification institutions. By analyzing the political processes linked to the establishment of these institutions, this paper aims to question the scope and performance of a form of regulation based on private governance, but also to ask whether forest governance is truly being increasingly privatized, as is often claimed. Through a review of literature, a look at statistics and surveys conducted in Brazil, we identify the limitations of governing through the market. We go on to analyze the linkages between public policy and private governance, highlighting the correlation between the performative nature of certification institutions and the prior filling of a certain number of gaps in public policies, especially in countries possessing tropical forest resources.